Enhanced synchronous photocatalytic 4-chlorophenol degradation and Cr(VI) reduction by novel magnetic separable visible-light-driven Z-scheme CoFe2O4/P-doped BiOBr heterojunction nanocomposites - Sin, J.-C. (Academic Press Inc., 2022)
The co-existence of organic contaminants and heavy metals including 4-chlorophenol (4-CP) and Cr(VI) in aquatic system have become a challenging task in the wastewater treatment. Herein, the synchronous photocatalytic decomposition of 4-CP and Cr(VI) over new Z-scheme CoFe2O4/PâBiOBr heterojunction nanocomposites were revealed. In this work, the nanocomposites were successfully developed via a surfactant-free hydrothermal method. The heterojunction interface was created by decorating magnetic CoFe2O4 nanoparticles onto PâBiOBr nanosheets. The as-fabricated CoFe2O4/PâBiOBr nanocomposites substantially improved the synchronous decomposition of 4-CP and Cr(VI) compared to the single-phase component samples under visible light irradiation. Particularly, the 30-CoFe2O4/PâBiOBr nanocomposite displayed the best photocatalytic performance, which decomposed 95.6 4-CP and 100 Cr(VI) within 75 min. The photocatalytic improvement was assigned to the Z-scheme heterojunction assisted charge migration between CoFe2O4 and PâBiOBr, and the acceleration of charge carrier separation was validated by the findings of charge dynamics measurements. The harmful 4-CP was photodegraded into smaller organics whereas the Cr(VI) was photoreduced into Cr(III) after 30-CoFe2O4/PâBiOBr photocatalysis, and the good recyclability of fabricated nanocomposite in photocatalytic reaction also showed promising potential for practical applications in environmental remediation. Finally, the radical quenching tests confirmed that there existed the Z-scheme path of charge migration in CoFe2O4/PâBiOBr nanocomposite, which was the mechanism responsible for its high photoactivity. Â© 2022 Elsevier Inc.